2003
DOI: 10.1136/vr.152.18.558
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A in the serum and milk of ewes with mastitis induced experimentally withStaphylococcusepidermidis

Abstract: Mastitis was induced experimentally in ewes with Staphylococcus epidermidis, and the concentrations of serum amyloid A (SAA) in milk and serum, and the somatic cell counts and bacteria in the milk were determined for up to 10 weeks in two experiments, each examining five infected and five control ewes. The somatic cell counts peaked eight hours after infection and preceded an increase in SAA in milk. A maximum concentration of 6460 microg/ml SAA was recorded in milk from the infected sheep, compared with a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
(30 reference statements)
4
16
1
Order By: Relevance
“…The findings showed that acute phase reaction developed in cows with subclinical mastitis and confirmed earlier observations reported by other authors (Winter et al 2003, Grönlund et al 2005, Eckersall et al 2006, Akerstedt et al 2007, Hiss et al 2007, Szczubiał et al 2008, Pyörälä et al 2011. Acute phase proteins are mainly produced in the liver, yet it was demonstrated that both SAA , Weber et al 2006 and Cp (Jaeger et al 1991, Cerveza et al 2000, Donley et al 2002 could also be produced in the udder.…”
Section: Discussionsupporting
confidence: 81%
“…The findings showed that acute phase reaction developed in cows with subclinical mastitis and confirmed earlier observations reported by other authors (Winter et al 2003, Grönlund et al 2005, Eckersall et al 2006, Akerstedt et al 2007, Hiss et al 2007, Szczubiał et al 2008, Pyörälä et al 2011. Acute phase proteins are mainly produced in the liver, yet it was demonstrated that both SAA , Weber et al 2006 and Cp (Jaeger et al 1991, Cerveza et al 2000, Donley et al 2002 could also be produced in the udder.…”
Section: Discussionsupporting
confidence: 81%
“…In a previous study, we found elevated levels of both haptoglobin and SAA in milk from udder quarters with sub-clinical mastitis 21 to 35 days after experimental infection with Staphylococcus aureus, but only SAA was significantly different from pre-infection levels [6]. Winter et al [22] also described elevated levels of SAA during sub-clinical experimentally induced Staphylococcus epidermidis mastitis in ewes. Several studies have also stated that healthy cows have very low, or undetectable, serum levels of SAA and haptoglobin [1][2][3]6], and this is also the case in milk from healthy quarters [3,6].…”
Section: Introductionmentioning
confidence: 90%
“…Whereas SAA levels in milk may be useful for the diagnosis on subclinical mastitis in individual ewes further studies are needed to determine its usefulness from bulk milk (Winter et al, 2006). Interestingly, opposite to bovine, the changes in the concentration of SAA in ewes with mastitis experimentally induced by Staphylococcus epidermidis are observed earlier in serum than in milk (Winter et al, 2003). In goats the studies are rather limited than in sheep.…”
Section: Apps In Small Ruminantsmentioning
confidence: 87%